PERAN TEKNOLOGI INFORMASI DALAM MENINGKATKAN EFEKTIVITAS SISTEM PEMERINTAHAN LOKAL DI ERA DIGITAL - Eko Yudianto Yunus; Nadinda Alvionita; Fitra Akbar Maulana; Muhammad Teguh Firmansyah (Journal of Innovation Research and Knowledge, 2024)
This research aims to analyze the role of information technology in increasing the effectiveness of local government systems in the digital era. Information technology (IT) is being adopted by local governments as a tool to simplify public services, speed up bureaucratic processes, and increase transparency. The research method used is qualitative with a descriptive approach. This study was conducted in Probolinggo City, where information technology has been implemented in various government sectors. The research results show that the use of IT can increase the efficiency of public services and public accessibility to information. However, there are still obstacles in terms of technological infrastructure and digital literacy that need to be overcome